Study on the contamination of najs mutawassitah in fish and water of the kuantan river - Rahman, Mohammad Mustafizur (2016)
Halal food should be free from najs (filth). The Kuantan River is very important in term of recreation, ecology and fish supply. It has a wide variety of fishes, which is regularly marketed for human consumption. It receives a lot of untreated sewage waste, which may carry enormous level of enteric bacteria. Therefore, a 12-month study was conducted to (i) investigate the occurrence of enteric bacteria (najs) contamination in water and fish and the variation of quality and quantity of enteric bacteria in water and fish in the Kuantan River, (ii) elucidate the relationship between water quality, and the quality and quantity of enteric bacteria in water and (iii) make recommendation based quality and quantity of enteric bacteria in water and fish. For the qualitative and quantitative estimation of bacterial load including enteric bacteria, 3 fish species namely chemparus (Cyclocheilichtys apogon), kawan (Labiobarbus festivus) and kerisi (Pristipomoides filamentosus) were collected by gill net from Kuantan River. Water and sediment samples were taken at 4 (four) zones: 5 km from the Kuantan River estuary insight sea, Kuantan River estuary, 5 km upstream from Kuantan River estuary and 10 km upstream of the Kuantan River estuary. Bacteria were cultured in both nutrient and marine agar plates. A molecular method (16S rRNA gene sequencing) was applied to identify all bacteria up to their genus/species level. Overall, chemparus (6.68×103 ± 0.74×103/g) had significantly higher (P<0.01) bacterial load compare to kawan (5.12×103 ± 0.60×103/g) and kerisi (5.20×103 ± 1.49×103/g). Bacterial load was significant higher (P<0.01) in gut than in gill and followed by skin of fishes. No serious pathogenic enteric bacteria were observed in fishes and therefore, fish are still safe for human consumption. Enteric bacteria were commonly observed in sediments and various layers of water column in all sampling zones. This gives evidence that Kuantan river water was contaminated with najs (filth). Mean bacterial load in water in Zone D was 5.8, 4 and 4.3 times higher than in Zone A, Zone B and Zone C, respectively. A significant negative relationship (r = - 0.742, P<0.01) was observed between salinity and bacterial load in the river water. Bacterial abundance in sediment in Zone D (8.38×106 ± 0.31×106/5g) was significant higher (P<0.01) than bacterial abundance in sediment in all other Zones (Zone A: 1.27×106 ± 0.31×106/5g, Zone B: 2.38×106 ± 0.61×106/5g and Zone C: 0.64×106 ± 0.35×106/5g). The mean dissolved inorganic nitrogen (DIN) concentration was significantly (P<0.05) lower in the monsoon months compared to other months. The mean DIN concentration in water in the sampling Zone near the Kuantan city (2.24±1.48 mg/l) was significantly higher than the mean DIN concentration (0.20±0.14 mg/l) in the upstream zone. Waste from Kuantan city is significantly influencing the growth of enteric bacterial (in water and sediment) and the water quality of the Kuantan River. The result of the study can be used for the proper management of the Kuantan River. Careful waste management by the Kuantan city authority may reduce enteric bacterial load in water and sediment and concentration of inorganic nitrogen in the Kuantan river water. These will help in increasing fish production and save the biodiversity of the river.